The School Property Tax and Homestead Credits: Accuracy, Equity, and Contribution to Overall Fiscal Relief - Steinberg, Matthew P.; Krupa Rifelj, Kelly; Fumia, Danielle; Allen, Vanessa (My University, 2007)
Property taxes are a visible and vital component of state and local government in Wisconsin. The authors contribute to the discussion of whether income tax credits designed to give property tax relief are accurate and equitable, and how the credits contribute to overall fiscal relief for median- and low-income Wisconsin residents with median-valued homes. The report analyzes the credit formulation; the distribution of relief among renters and between renters and homeowners; and the makeup of overall fiscal relief since 1991(92) through the credits and assistance to local governments.